2014
DOI: 10.4321/s1130-01082014000100002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the adequacy and diagnostic accuracy of the histology samples obtained with a newly designed 19-gauge EUS histology needle

Abstract: Background: Endoscopic ultrasound (EUS)-guided fine needle aspiration (FNA) is an accurate technique for sampling intraintestinal and extraintestinal lesions. However, cytology possesses certain limitations, which may be overcome if histological specimens are provided to the pathologist.Aim: The aim of the study was to evaluate the accuracy of a newly developed 19G histology needle.Methods: Retrospective analysis of a prospectively collected data base including patients who underwent EUS-guided biopsy with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…Their recommendations, however, are not evidence based and there are no studies directly comparing commercially available needles. Indeed, as shown in the present study and in the previous multicenter published experience (24,28), use of the 19G Procore TM is associated with very high technical success and performance rates even, when used transduodenally by expert endosonographers. Despite these results the use of a particular needle will likely be based upon personal preference of the echoendoscopist until more definitive data will become available.…”
Section: Published In This Issue Of the Revista Española De Enfermedasupporting
confidence: 78%
See 2 more Smart Citations
“…Their recommendations, however, are not evidence based and there are no studies directly comparing commercially available needles. Indeed, as shown in the present study and in the previous multicenter published experience (24,28), use of the 19G Procore TM is associated with very high technical success and performance rates even, when used transduodenally by expert endosonographers. Despite these results the use of a particular needle will likely be based upon personal preference of the echoendoscopist until more definitive data will become available.…”
Section: Published In This Issue Of the Revista Española De Enfermedasupporting
confidence: 78%
“…Another important aspect is the best way to process the specimens obtained with EUS-FNB (30). As pointed out by Iglesias-Garcia et al (28), in the first feasibility study using the 19G Procore TM (24) each of the participating centers did not apply a uniform protocol to retrieve the sample from the needle (some by reinserting the stylet, others by flushing with saline) and to prepare the sample before processing in the pathology lab [samples were placed in formalin or in a liquid-based preparation, ThinPrep ® (hologic Corp, Bedford, MA)]. Interestingly, the interobserver agreement among five expert pathologists in grading the quality of specimens obtained in the five participating centers was found to be excellent and particularly high (91.2 %) with regard to sample adequacy, with a Fleiss' κ of 0.73 (95 % CI 0.61-0.81) (31).…”
Section: Published In This Issue Of the Revista Española De Enfermedamentioning
confidence: 82%
See 1 more Smart Citation
“…Consistent tissue core acquisition with EUS‐guided biopsy has recently been achieved through the development of new side‐ and end‐cutting EUS needles, with different mechanisms, calibers and design . The Quick‐Core needle (Cook Medical, Bloomington, IN, USA) is a 19‐G‐Tru‐Cut biopsy needle; the 19‐ and 22‐G ProCore needles have a lateral opening with reverse‐bevel technology . A meta‐analysis of nine studies showed no significant differences between the 22‐G ProCore and the standard 22‐G FNA needles in diagnostic adequacy, accuracy, or histological core specimen acquisition .…”
Section: Interventional Eus: New Tools New (And Old) Applicationsmentioning
confidence: 99%
“…53 The Quick-Core needle (Cook Medical, Bloomington, IN, USA) is a 19-G-Tru-Cut biopsy needle; 54 the 19-and 22-G ProCore needles have a lateral opening with reverse-bevel technology. 55,56 A metaanalysis of nine studies showed no significant differences between the 22-G ProCore and the standard 22-G FNA needles in diagnostic adequacy, accuracy, or histological core specimen acquisition. 57 Recently, other types of needle, specifically conceived for EUS-FNB, have become available.…”
Section: Fusion Imagingmentioning
confidence: 99%